Desain Pangan Instan Gizi Khusus Lansia Berbasis Binte Biluhuta Diperkaya Nanomineral Tulang Ikan - Bambang Riyanto; Wini Trilaksani; Vegatarani Aulia Azzahra (Universitas Sriwijaya, 2020)
Various instant foods for the elderly began to be developed. Binte biluhuta is an indigenous nusantara soup from Gorontalo with the main ingredient are corn and skipjack. The unique characteristic of soup is potential became special food that can be served for elderly, how ever the calcium content that is very low and the presence of oxalic acid still being abstacle. Fish bone was a natural source of calcium. The research objectives were to design special nutrient instant food for elderly based on binte biluhuta indigenous food from Gorontalo enriched with fish bone nanomineral. The research included calcination of fish bones at a temperature of 600 ?C for 6 hours and reduced the size with nanomilling became nanomineral. Binte biluhuta cream soup was designed according to the Recommended daily intake (RDI) of the elderly. Characteristics quality was determined in order to develop microwave cooking. Particle size of nanomineral catfish bone was 70-100 nm, white color and contained 852000 ± 15.08 mg/Kg calcium, phosphorus 146300 ± 43.89 mg/Kg and magnesium 4410 ± 0.44 mg/Kg. Binte biluhuta instant cream soup with rasio of corn and fish 15: 1 served using microwave cooking and fortified 0.84 g nanomineral fish bone from 30 g binte biluhuta instant cream soup, contained 57470.39 ± 57.87 mg/Kg amino acids and 1.08 ± 0.06 mg/Kg oxalic acid. Binte biluhuta instant cream soup as much 30 g can fulfilled the needs of elderly calcium 51.47% and energy 88.65 Kcal.